Molecular Basis of Stationary Phase Survival and Applications - Jaishankar, Jananee; Srivastava, Preeti (Frontiers in Microbiology, 2017)
Stationary phase is the stage when growth ceases but cells remain metabolically active. Several physical and molecular changes take place during this stage that make them interesting to explore. The characteristic proteins synthesized in the stationary phase are indispensable as they confer viability to the bacteria. Detailed knowledge of these proteins and the genes synthesizing them is required to understand the survival in such nutrient deprived conditions. The promoters, which drive the expression of these genes, are called stationary phase promoters. These promoters exhibit increased activity in the stationary phase and less or no activity in the exponential phase. The vectors constructed based on these promoters are ideal for large scale protein production due to the absence of any external inducers. A number of recombinant protein production systems have been developed using these promoters. This review describes the stationary phase survival of bacteria, the promoters involved, their importance, regulation and applications.